Biochemical and in silico inhibition of bovine and human carbonic anhydrase-II by 1H-1,2,3-triazole analogs - Khan, Majid; Avula, Satya Kumar; Halim, Sobia Ahsan; Waqas, Muhammad; Asmari, Mufarreh; Khan, Ajmal; Al-Harrasi, Ahmed (Frontiers in Chemistry, 2022)
A series of 1H-1,2,3-triazole analogues (7a-7d and 9a-9s) were synthesized via “Click” chemistry and evaluated for in vitro carbonic anhydrase-II (bovine and human) inhibitory activity. The synthesis of intermediates, 7a and 7c were achieved by using (S)- (-) ethyl lactate as a starting material. These compounds (7a and 7c) underwent Suzuki-Miyaura cross-coupling reaction with different aryl boronic acids in 1,4-dioxane, reflux at 90-120 °C for 8 h using Pd(PPh3)4 as a catalyst (5 mol%) and K2CO3 (3.0 equiv) / K2PO4 (3.0 equiv) as a base to produce target 1H-1,2,3-triazole molecules (9a-9s) in good yield of 67-86%. All the synthesized compounds were characterized through NMR spectroscopic techniques. Furthermore, all those compounds have shown significant inhibitory potential for both sources of carbonic anhydrase-II (CA-II). In the case of bCA-II; compounds 9i, 7d, 9h, 9o, 9g, and 9e showed potent activity with IC50 values in the range of 11.1 – 17.8 µM. Whereas, for hCA-II; compounds 9i, 9c, 9o, and 9j showed potent potential with IC50 values in the range of 10.9 – 18.5 µM. Preliminary Structure-Activity Relationship (SAR) recommend that the presence of 1H-1,2,3-triazole moiety in those synthesized 1H-1,2,3-triazole analogues (7a-7d and 9a-9s) significantly contributes to the overall activity. However, several substitutions on this scaffold affect the activity to several folds. Selectivity index showed that compounds 9c, 9k, and 9p are selective inhibitors of hCA-II. Kinetics studies showed that these compounds inhibited both enzymes (bCA-II and hCA-II) in competitive manner. Molecular docking indicates that all the active compounds fit-well in the active site of CA-II. This study has explored the role of 1H-1,2,3-triazole containing compounds in the inhibition of CA-II to combat CA-II related disorders.